The importance of the use of technological tools for the teaching and learning of foreign languages - Segovia López, Karen Abigail; Cañas López, Paulina Elizabeth (2024)
This course helped all students to improve their knowledge in the use of technology for language teaching and thus be able to transmit their knowledge acquired during the specialization course to new generations. It is important to mention that it helps students to improve their capacities and explore the use of technology in the classroom to apply in the new learning modality. The main objective of this course was to teach students how to use technological tools to create and design material that could be useful in online education, nowadays in online classrooms. The materials created in this course were from an educational infographic to a google site, where all the knowledge acquired during the course time was applied. Also, at the end of the course is important to mention that the specialization course is a new option for future graduates to enroll in as a substitute for the traditional graduation work, also known as thesis. This modality could open more opportunities to students to develop new skills using technology to apply in the teaching-learning process. Key words: Technological Tools ; Online Learning ; Synchronous ; Asynchronous ; Online English Language Teaching